The effect of growth regulators, Zolfast preparation and between them in protein components of two cultivars of wheat grains (IPAA-99 and Tamuze-2). - Yaseen, Abdulameer Ali; Hussein, Hassanein Abdul Hussein (Al-Qadisiyah Journal of Pure Science, 2017)
The experiment was conducted during the winter season of the year (2010 - 2011) in Department of Biology / College of Education /AL - Qadisiya University, to study the impact of two growth regulators (Gibberellic acid GA3 and Benzyladenine BA), Zolfast and interaction between them on protein components of two cultivars of wheat grains, Triticum aestivum L. (IPAA-99 and Tamuze-2). The experiment was designed as Randomized Complete Blocks with three replicates in a factorial arrangement of three factors (5 Ã— 3 Ã— 2). The first factor included five concentrations of growth regulators; (0Control, 25GA3, 50GA3, 100BA and 150BA) mg /L. The second factor included three concentrations of Zolfast (0, 1 and 2) ml /L, while the third factor was the two cultivars of wheat (IPAA-99 and Tamuze-2). The Revised Least Significant Difference (RLSD) at 0.05 probability was used to compare treatment means, whenever treatments affects were evident. Hand sprayer was utilized to spray all concentrations of growth regulators and Zolfast, twice during the growing season. The first was one month after seed sowing (during the 4-5 true leaves), and the second was after two months. The following parameters were measured during the study total protein percentage, wet and dry gluten, and percentage of gliadin, glutenin and gluten were measured by using (HPLC) technique. Results showed: 1- BA was superior GA3 in all studied characteristics, as well as with Zolfast which gave on least concentration (1 ml/L) higher content of proteins compared to higher concentration; in addition to Tamuze-2 cultivar was superior compared to IPAA-99 in most parameters. 2- All interactions between the studied factors a significant increase in the protein components of wheat cultivars, especially with both concentration of BA and low concentration of Zolfast. 3- The triple interaction between factors included in the experiment revealed a significant effect on all parameters studied, IPAA-99 had higher glutenin% when treat cultivar with (150mg/L BA + 1ml/L Zolfast). While Tamuze-2 had higher gliadin and gluten% when treated with (150mg/L BA + 1ml/L Zolfast) and Total protein% was increased with the use of (50mg/L GA3 + 2ml/L Zolfast) and with (150mg/L BA + 2ml/L Zolfast).